Individual quarter dry-off procedure in dairy cows - Ibarguren, Clara, author; Pinedo, Pablo, advisor; Velez, Juan, committee member; Lombard, Jason, committee member (Colorado State University. Libraries, 2025)
Mastitis, defined as inflammation of the mammary gland, has a major impact on the dairy industry, affecting profitability and animal welfare due to reduced milk production, increased antibiotic use, and pain and discomfort in the affected animals. This health disorder concerns researchers, producers, and consumers worldwide. The "individual quarter dry-off" procedure, which consists of stopping milking the affected quarter is an alternative to the use of antibiotic treatment in unresponsive cases. Understanding the relationship between the multiple factors involved in the disease and this procedure is crucial. Through an extensive review of mastitis and a descriptive statistical analysis of this dry-off practice, this thesis focuses on understanding the dynamics of this procedure within a lactating dairy herd. Chapter 1 includes a literature review on mastitis, and the possible management practices conducted by the dairy industry to mitigate the problem. Due to the limited information available on individual quarter dry-off, the information provided in this chapter consists of a discussion of the anatomy of the mammary gland, physiology, pathology of mastitis disease, and management practices. Once general knowledge of the root of the problem is established, technical implications regarding the individual dry-off procedure are explained in the following chapter. The objective of chapter 2 is to describe the dynamics of individual quarter dry-offs in certified organic dairies. The data were collected from PCDart (©DRMS) spanning from 2018 to 2023 from four organic dairies in CO, USA. The dataset included 2,881 cows with at least one dried quarter (QDO), of which 769 cows (26%) had a second dried quarter (QDO2). The variables considered in this study were quarter location, parity, days in milk (DIM), season, and survival after the first quarter dry-off (QDO). The statistical analysis was completed in SAS (SAS Institute Inc.), employing chi-square goodness of fit, logistic regression, and ANOVA. The results showed that QDO was more prevalent in front quarters among both primiparous (PP) and multiparous (MP) cows, with higher frequencies observed during winter across both parity categories. The mean ± SE of days in milk at QDO was smaller for primiparous cows compared to multiparous cows, and it took approximately one year to have a second dried quarter to occur. Parity category had no effect on the likelihood of QDO2, and the number of days to culling after QDO were not significantly different between parities, averaging around 365 days. Additionally, cows with QDO had lower actual and projected 305 milk yield compared to healthy cows (597 kg [PP] and 436 kg [MP] less for actual 305 milk production; 628 kg [PP] and 495 kg [MP] less for projected 305 milk production). Overall, milk yield was consistently lower in cows with QDO compared to their herdmates. These findings provide valuable insights into the dynamics of quarter dry-off, contributing novel information to support the control of mastitis in certified organic dairies. Chapter 3 explores the dynamics of milk yield following the individual dry-off of quarters (QDO) in dairy cows. The study focused on cows that had one quarter dried off due to a chronic mastitis event and had milking records available for 30 days post-procedure. Data were collected from 144 cows on an automatic milking system (AMS) dairy farm in Colorado, of which 79% (n=144) were multiparous and 21% (n=30) primiparous. Information was sourced from DelPro and DairyComp on-farm software, and linear mixed models with repeated measures and estimated marginal means (emmeans) were generated using RStudio. Although the sample size of primiparous cows was limited, results showed a slight decrease in milk production following QDO. Conversely, multiparous cows displayed increased production in the opposite quarters, with an overall milk yield rising over the 30-day period after the dry-off. Total milk production following QDO was higher in cows ≤120 days in milk (DIM) compared to those with >120 DIM. Additionally, cows experienced greater milk yields when the dry-off procedure was performed on rear quarters versus front quarters. Of the variables analyzed, the number of days in milk after the procedure showed the most statistically significant relationship with milk production, while presence of other diseases did not exhibit a significant effect. These findings offer valuable insights into milk yield dynamics and implications for management strategies in dairy herds.